Sifat Fisik Bata Beton Dengan Penambahan Styrofoam - Herol, Herol; Djauhari, Zulfikar; Ismeddyanto, Ismeddiyanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Indonesia is a country with a high seismic activity. Due to this reason, constructions in Indonesia must pay attention to every aspect, including the design, the construction process and materials. The use of concrete bricks on the wall has an impact on the loading of a structure. This research aimed to determine the effect of addition of styrofoam to the weight, density, water absorption and porosity of the concrete bricks. In this study, the composition of the mixture used was 1 cement : 3 sand with the variations of styrofoam as a substitute for sand at 0%, 5%, 10% and 15%. Test results showed that the average weight of concrete brick with 0% of styrofoam was 2.42 gr/cm3, 5% of styrofoam was 2,31 gr/cm3, 10% of Styrofoam was 2.29 gr/cm3, and 15% of styrofoam was 2.22 gr/cm3. The porosity of the concrete brick with 0% of styrofoam was 7.89%, 5% of styrofoam was 7.66%, 10% of styrofoam was 6.81%, and 15% of styrofoam was 4.62%. From water absorption test, the results showed that the average value of concrete brick with 0% of styrofoam was 3.70%, 5% of styrofoam was 3.63%, 10% of styrofoam was 3.34%, and 15% of styrofoam was 2.32%. The more styrofoam is added, the more the weight and density of the concrete was decreasing. The porosity and water absorption values of the concrete bricks was decreasing with the addition of styrofoam due to the waterproof property of styrofoam. The result of water absorption test showed that all concrete bricks tested were concrete bricks with quality I, that are concrete brick used for load bearing construction and are commonly used for unprotected construction (outside the roof) because of having a water absorption value smaller than 25%. Keywords: Concrete brick, styrofoam, weight, density, water absorption, porosity